Empowering Smart Megacities: IoT-Based Smart Metering for Enhanced Energy Efficiency and Consumer Empowerment - Rithesh P Karkera; Abhishek S Athalekar; Gajanan Thokal; Suyash Pawar (Science & Technology Asia, 2025)
The development of smart homes, societies, communities, and metropolises has assumed a central role in the recent era of IoT-based intelligent devices. The development of the smart grid, an intelligent infrastructure for managing electricity, is a top priority for smart megacities in particular. Bidirectional communicating smart meters are at the heart of this infrastructure; they are more than just a convenience. By giving customers better information and control over their energy consumption and appliances, these modern iterations of conventional energy meters empower consumers. These features offer new levels of interaction, from remote control of home appliances to real-time consumption data. However, the use of reprogrammable microcontrollers like the Arduino Uno and Node MCU is required to implement such a capability. These microcontrollers aid manufacturers in modifying products to meet shifting consumer demands and stay relevant over time. Smart meters, the foundation of Smart Grids, coordinate the smooth operation of online devices, effectively manage energy consumption, and promote significant energy conservation. We present a novel IoTbased smart metering paradigm in accordance with this viewpoint. In addition to archiving these data for use in calculating monthly electricity bills, this gives consumer’s power by sending them real-time energy use statistics over 24-hour cycles via SMS. This comprehensive approach fosters a culture of energy conservation, which is urgently needed in our day and age, while also empowering consumers to manage their electricity consumption. The system demonstrated an energy measurement accuracy of 97.91%, with only a 2.0833% error, as validated against multimeter readings.